Effectiveness of Origami Therapy in Reducing Anxiety among Hospitalized Children: A Quasi-Experimental Study - B. Mahalakshmi; N. Siva Subramanian; Pinalben Chandreshbharthi Goswami; Dhruvkumar Savjibhai Chaudhary; Shylaja Kailash Attur; Kailash Attur (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Hospitalization is a stressful experience for children, often resulting in anxiety that affects their emotional well-being and recovery. Non-pharmacological interventions, such as origami therapy, have shown potential for managing anxiety in paediatric care. Objective: To evaluate the effectiveness of origami therapy in reducing anxiety levels among hospitalized children aged 6-10 years. Materials and Methods: Qasi-experimental pre-test and post-test control design was used. Sixty participants were divided into experimental group (30-minute origami therapy for seven days) and control group (standard hospital care). Anxiety levels were measured pre- and post-intervention using validated behavioural observation checklist. Results: Experimental group demonstrated significant reduction in anxiety levels after intervention (P < 0.001), whereas control group showed no significant changes (P > 0.05). Conclusion: Origami therapy is effective, simple, and engaging non-pharmacological intervention for reducing anxiety in hospitalized children. Its application in paediatric care can enhance the emotional well-being of young and improve overall hospital experience.